Counseling, health services and training of dental in Suka Makmur Binjai - Abidin, Trimurni; Panggabean, Sondang Pintauli; Farahanny, Wandania (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
This paper explains the community service activities in Suka Makmur Village, Binjai District, Langkat Regency. The aim is to improve the quality of life of the community through oral health, which is to encourage the emergence of creativity and initiative of each individual or community group in the village of Suka Makmur. Communities actively participate in health programs in their villages, and determine program priorities according to the needs and desires of the community. Overall it can be seen that 95.4% of the population experienced a low caries experience category, 3.8% of them had a moderate caries category and there were already 0.9% of the population who had a high caries risk category.